University autonomy: A historical overview and contextual analysis in Vietnam - Chau, Hoang Ngoc Minh; Thu, Tran Thi Anh (Edelweiss Applied Science and Technology, 2025)
University autonomy has become a pivotal issue in the context of global efforts to improve higher education's contribution to social equity and socio-economic progress. In the field of higher education, the creation and dissemination of knowledge play a crucial role in promoting social equity and socio-economic development. This paper focuses on the role of university autonomy in addressing the emerging challenges and opportunities facing higher education. By employing content analysis and drawing upon secondary sources, the paper outlines the historical development and characteristics of university autonomy models worldwide and in Vietnam. Policy measures implemented to encourage university autonomy in Vietnam are also discussed in detail. Additionally, the paper provides a comprehensive overview of the current state of university autonomy by reviewing relevant academic studies. In the discussion and conclusion, the paper highlights the critical importance of collaboration and consensus from the educational community and society at large in fostering university autonomy. Only with such support can a truly autonomous higher education environment flourish and adequately meet the increasing demands of society.